Clinical Outcomes of Conventional Fistulotomy versus Ligation of Intersphincteric Fistula Tract in Patients with Fistula-in-ano: A Prospective Interventional Study - R Sahasra Serisha; Jayakanthan Saravanan; P Suganya (International Journal of Anatomy Radiology and Surgery)
Introduction: Fistula-in-ano is a common anorectal condition that poses significant challenges for surgical management, with the primary concern being the preservation of sphincter function and prevention of complications such as recurrence and incontinence. Two common surgical procedures for managing fistula-in-ano are conventional fistulotomy and the Ligation of Intersphincteric Fistula Tract (LIFT) procedure. Fistulotomy is considered the gold standard for treatment but carries risks, including delayed wound healing and the potential for postoperative fecal incontinence. The LIFT procedure, which was introduced as a sphincter-preserving alternative, offers advantages such as reduced pain, quicker recovery, and lower risk of incontinence, particularly in anal fistulas involving the external sphincter. Aim: To compare the clinical outcomes of fistulotomy versus LIFT in fistula-in-ano. Materials and Methods: A prospective interventional study was done in a total of 62 patients at Sree Balaji Medical College and Hospital, Chennai, Tamil Nadu, India with fistula-in-ano for a duration of 18 months. Among them, 31 patients underwent conventional fistulotomy (Group I), and 31 underwent the LIFT procedure (Group II). Key outcome measures included wound healing time, infection rates, postoperative pain, recurrence rates, and patient satisfaction. Categorical variables were compared using Chi-square tests, while continuous variables were compared using independent t-tests. A p-value of less than 0.05 was considered statistically significant. Results: The study found that LIFT patients experienced faster wound healing, with a statistically significant p-value of 0.003. They also had fewer infections, with 38.7% of patients developing an infection in conventional fistulotomy group compared to 16.1% in the LIFT group (p=0.002). Additionally, lower rates of incontinence were observed; 6.5% of patients in the conventional fistulotomy group reported mild incontinence (Wexner score of 2-4), while none of the patients in the LIFT group reported any significant incontinence (Wexner score of 1) (p=0.018). Conclusion: The findings support the use of LIFT as a viable alternative to conventional fistulotomy, especially in cases where sphincter preservation is critical. This study highlights the need for individualised treatment approaches to optimise patient outcomes in the surgical management of fistula-in-ano.